2017
DOI: 10.1002/2017gl075443
|View full text |Cite
|
Sign up to set email alerts
|

Climate and Anthropogenic Controls of Coastal Deoxygenation on Interannual to Centennial Timescales

Abstract: Understanding dissolved oxygen variability in the ocean is limited by the short duration of direct measurements; however, sedimentary oxidation‐reduction reactions can provide context for modern observations. Here we use bulk sediment redox‐sensitive metal enrichment factors (MoEF, ReEF, and UEF) and scanning X‐ray fluorescence records to examine annual‐scale sedimentary oxygen concentrations in the Santa Barbara Basin from the Industrial Revolution (Common Era ~1850) to present. Enrichments are linked to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Waters below the deepest sill are dysaerobic (dissolved oxygen < 0.1 ml liter −1 ) between flushing events (Bernhard and Reimers, 1991). Flushing event frequency of deep water is driven by interannual climate (ENSO) variability, which switches the basin between a stagnant water column and a ventilated one, a process that amplifies variability in the magnitude of oxygen depletion (Bograd et al, 2002;Wang et al, 2017).…”
Section: Main Stem Of Chesapeake Bay (Cb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Waters below the deepest sill are dysaerobic (dissolved oxygen < 0.1 ml liter −1 ) between flushing events (Bernhard and Reimers, 1991). Flushing event frequency of deep water is driven by interannual climate (ENSO) variability, which switches the basin between a stagnant water column and a ventilated one, a process that amplifies variability in the magnitude of oxygen depletion (Bograd et al, 2002;Wang et al, 2017).…”
Section: Main Stem Of Chesapeake Bay (Cb)mentioning
confidence: 99%
“…Bottom water oxygen in the basin has been decreasing since about 1850 due to upper ocean warming (decreases in solubility and vertical mixing) (Wang et al, 2017), and the frequency and duration of hypoxia in California Current waters has been increasing as the Eastern Pacific oxygen minimum zone expands (Stramma et al, 2010;Wang et al, 2017). The spatial extent of oxygen depleted deep water is estimated to be on the order of 800 km 2 .…”
Section: Main Stem Of Chesapeake Bay (Cb)mentioning
confidence: 99%
“…It has also been noted that decreases in oxygen outside the basin appeared to be more pronounced during January to March (Bograd et al, 2008), which is the time period immediately preceding the detection of spring flushing events in the CalCOFI time series. Finally, paleoceanographic evidence using Fe/Ti ratios from sediment cores collected in the basin suggest oxygen concentrations in the bottom waters over the past 15 years are the lowest observed over the last 200 years (Wang et al, 2017). A recent analysis of oxygen trends in the global ocean concluded that oxygen has decreased in the ocean's interior due to greater apparent oxygen utilization, which points to changes in biology or ocean physics as the primary cause of this decrease rather than decreased solubility in the surface ocean (Ito et al, 2017).…”
Section: External Influences On Bottom Water Biogeochemistrymentioning
confidence: 95%
“…Basin has well-documented sediment laminations through most of the Holocene indicating persistent low oxygen, but also shows gradual intensification of the oxygen minimum zone within SBB since 1850 (Wang et al, 2017).…”
mentioning
confidence: 99%
“…In the last 150 years, deoxygenation is synchronous across SBB, SMB and SDM. In this interval, decreases in oxygenation are potentially due to an increase in organic carbon supply from terrestrial sources due to human land use change in the Southern CA region (Tomasovych and Kidwell, 2017;Wang et al, 2017). Investigation of oxygenation change over time requires further research to identify forcing mechanisms for changes in the upper margin of the OMZ and to discern the relative impact of human and natural forcing in changing 435 oxygenation across the last century.…”
mentioning
confidence: 99%